VANDAL BEHAVIOUR OF ADOLESCENTS AS A LEGAL AND PSYCHOLOGICAL PROBLEM - O. V. Gurova (Russian State Vocational Pedagogical University, 2018)
Introduction. In today's world, a problem of vandalism has become rather widespread. Vandals damage monuments of cultural heritage, historic sights and other types of public space. A theoretical aspect of vandalism is registered in jurisprudence, which is guided principally by regulatory approach to the solution of questions of the violation of laws and recognised rules of human coexistence. However, focusing only on the application of administrative and criminal sanctions to those guilty of vandal offenses, does not allow reducing the excessive number of universal manifestations of vandalism, which have been increased recently, by avoiding psychological factors. The aims of the publication were the following: to actualise and discuss the problem of vandal behaviour among adolescents; to denote a problem field of psychological research, which is necessary for identifying genesis, vandal determination and further organisation of effective preventive activity in educational institutions.Methodology and research methods. The methodological basis of the research involved hermeneutic and dialectic approaches, general scientific methods of analysis, synthesis, comparison and synthesis of scientific data.Results and scientific novelty. The author attempted to interpret the problem of vandal behaviour of adolescents from the point of view of interdisciplinary understanding. The author highlighted the need for a detailed psychological analysis of the phenomenon under study, its causes and predictors for the formation of adequate measures to reduce the spread of vandalism in the public space. The contradictions in the psychological theory, educational practice and consciousness of society were revealed: between the widespread occurrence of acts of vandal behaviour and the limited methods and means to prevent it; between the mass involvement of adolescents in vandalism and the lack of specialised age-based programmes to correct vandal behaviour; between the prevalence of unauthorized graphic activity of schoolchildren and other forms of vandal behaviour in the educational environment and the reluctance of teachers and administration of educational institutions to recognise this as a noteworthy problem; between the social significance of determination of lawful and effective punishment (in terms of prevention) and insufficient attention to personal reasons that encourage a person to commit or not to commit vandal acts; between common scientific interest in the individual psychological and socio-typological features of adolescents committing vandalism and inadequate attention to the socio-psychological motivational determinants, initiating and forming the readiness to commit vandal actions. The outlined discrepancies allowed the author to plan a general trajectory of the required research, in which the phenomenon of vandalism has to be considered in the context of realisation of personal subjectivity.Practical significance. It is known that small forms of vandal behaviour can be transformed to heavier types of destructive behaviour, right up to antisocial ones. Nevertheless, the ambiguous perception of vandal acts in society and scientific community, lack of a clear boundary in understanding of acceptability or unacceptability of kinds of this phenomenon is interfered with creation of effective model of counteraction of its expansion. On the one hand, the designated direction of scientific search can generate knowledge of essence of such deviant behaviour as vandalism, and, on the other hand, vandalism has the practice-focused importance as it can establish the foundation for the development of approaches of educational influence, which prevent the manifestations of vandalism.